35Cl solid-state NMR spectroscopy of HCl pharmaceuticals and their polymorphs in bulk and dosage forms. Issue 33 (14th July 2016) - Namespetra, Andrew M.; Hirsh, David A.; Hildebrand, Marcel P.; Sandre, Anthony R.; Hamaed, Hiyam; Rawson, Jeremy M.; Schurko, Robert W.
Abstract : Herein, we demonstrate the use of 35Cl SSNMR for the structural fingerprinting of HCl salts of pharmaceuticals in both bulk and dosage forms. Abstract : Herein, we demonstrate the use of 35 Cl solid-state NMR (SSNMR) at moderate (9.4 T) and high (21.1 T) magnetic field strengths for the structural fingerprinting of hydrochloride (HCl) salts of active pharmaceutical ingredients (APIs) and several polymorphs, in both bulk and dosage forms. These include salts of metformin, diphenhydramine, nicardipine, isoxsuprine and mexiletine (the crystal structure of a mexiletine polymorph is reported herein). Signal-enhancing pulse sequences utilizing frequency-swept pulses and broadband cross polarization were employed to significantly decrease experimental times. In most cases, powder X-ray diffraction (pXRD) patterns and 13 C SSNMR spectra are not useful for characterizing the APIs in dosage forms, due to interfering signals from the excipients ( e.g., fillers and binders). However, it is demonstrated that 35 Cl SSNMR can be used independently to fingerprint individual APIs and to detect the nature of the solid phases in the dosage forms without interference from the excipient. 35 Cl SSNMR experiments were also conducted on systems with multiple polymorphs ( i.e., isoxsuprine HCl and mexiletine HCl), and the solid phases of these APIs in their dosage forms are identified. 35 Cl EFG tensors obtained from plane-wave DFT calculations on model systems are also presented and discussed in the context of their relationship to the local hydrogen-bonding environments of the chloride ions. This methodology shows great promise for identification of solid phases and detection of polymorphs and impurities, which are matters of importance for quality assurance in the pharmaceutical industry.